Answer: 1682
(45 x 36) + 62
1620 + 62 = 1682
Answer:
Step-by-step explanation:
1) 4x -3
x = -7 ;
4x - 3 = 4*(-7) - 3 = - 28 - 3 = -31
x = 14 ;
4x - 3 = 4*14 - 3 = 56 - 3 = 53
x = 0
4x - 3 = 0 - 3 = -3
2) 6 -3x
x = -7 ;
6 - 3x = 6 - 3*(-7) = 6 + 21 = 27
x = 14
6 - 3x = 6 - 3*14 = 6 - 42 = -36
x = 0
6 - 3x = 6 - 0 = 6
![3) \dfrac{3x - 21}{7}\\\\x = -7\\\\\\\dfrac{3*(-7)-21}{7}=\dfrac{-21-21}{7}=\dfrac{-42}{7}=-6\\\\\\x = 14\\\\\dfrac{3*14-21}{7}=\dfrac{42-21}{7}=\dfrac{21}{7}=3\\\\\\x=0\\\\\dfrac{0-21}{7}=\dfrac{-21}{7}=-3\\\\](https://tex.z-dn.net/?f=3%29%20%5Cdfrac%7B3x%20-%2021%7D%7B7%7D%5C%5C%5C%5Cx%20%3D%20-7%5C%5C%5C%5C%5C%5C%5Cdfrac%7B3%2A%28-7%29-21%7D%7B7%7D%3D%5Cdfrac%7B-21-21%7D%7B7%7D%3D%5Cdfrac%7B-42%7D%7B7%7D%3D-6%5C%5C%5C%5C%5C%5Cx%20%3D%2014%5C%5C%5C%5C%5Cdfrac%7B3%2A14-21%7D%7B7%7D%3D%5Cdfrac%7B42-21%7D%7B7%7D%3D%5Cdfrac%7B21%7D%7B7%7D%3D3%5C%5C%5C%5C%5C%5Cx%3D0%5C%5C%5C%5C%5Cdfrac%7B0-21%7D%7B7%7D%3D%5Cdfrac%7B-21%7D%7B7%7D%3D-3%5C%5C%5C%5C)
4)
![\dfrac{3x}{7}-21\\\\\\x = -7\\\\\dfrac{3*(-7)}{7}-21=-3-21=-24\\\\\\x =14\\\\\dfrac{3*14}{7}-21=3*2-21=6-21=-15\\\\\\x=0\\\\\dfrac{0}{7}-21=-21](https://tex.z-dn.net/?f=%5Cdfrac%7B3x%7D%7B7%7D-21%5C%5C%5C%5C%5C%5Cx%20%3D%20-7%5C%5C%5C%5C%5Cdfrac%7B3%2A%28-7%29%7D%7B7%7D-21%3D-3-21%3D-24%5C%5C%5C%5C%5C%5Cx%20%3D14%5C%5C%5C%5C%5Cdfrac%7B3%2A14%7D%7B7%7D-21%3D3%2A2-21%3D6-21%3D-15%5C%5C%5C%5C%5C%5Cx%3D0%5C%5C%5C%5C%5Cdfrac%7B0%7D%7B7%7D-21%3D-21)
Answer:
D. 2
Step-by-step explanation:
rise/run =
=
= 10/5 = 2
The <em>correct answer</em> is:
D) reflect over the y axis and then reflect again over the y axis.
Explanation:
Logically, if we reflect a figure across the y-axis and then reflect across the y-axis again, we have undone what we originally did, and the figure is back in its original position.
Algebraically, reflecting across the y-axis maps every point (x, y) to (-x, y). Reflecting this point across the y-axis maps (-x, y) to (x, y); this is our original point.
So,
We can notice that the graph of g, is translated 2 units to the left and 4 units up. We can express these changes with the following equation: